Planning a state wide forest inventory of Sarawak with emphasis on appropriate sampling design - Mohd Bohari, Ahmad Ashrin; Suhaili, Affendi; Awang Zulkifli, Awang Arifin; Wan Mohd, Wan Razali (Jabatan Perhutanan Semenanjung Malaysia, 2011)
Statistics derive from a forest inventory are key information when managing valuable forest resources. Hence, accurate and latest information on forest resources is crucial and critical to obtain in order to prepare the Sustainable Forest Management plans over the forest area in Sarawak. In Sarawak, three types of forest inventory were carried out in the last 40 years, i.e. Forest Resource Inventory (FRI), Forest Management Inventory (FMI) and Forest Operational Inventory (FOI). In view that the existing inventories had been used for last 40 years, Forest Department Sarawak is planning to review and develop an accurate and appropriate new sampling design for the current and future inventories of its forest resources. This study in collaboration with Universiti Putra Malaysia is to support the development of efficient sampling design for forest inventories in Sarawak.